Proses Pengolahan Minyak Mentah di Unit Kilang PPSDM MIGAS CEPU - Istiqomah, Ilmi Nurul; Maghfiroh, Amalia Ma’rifatul (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
One of the industrial sectors that can be in the engineering field is the oil processing industry. Crude oil obtained from the earth can of course be used directly for daily needs such as cooking or for vehicle fuel. The oil needs to be processed so that it becomes suitable for use according to the needs to be used. This oil processing is carried out in a place called a refinery. At PPSDM Migas Cepu there is a refinery unit that processes crude oil into several oil products including residue, diesel and pertasol. The processing process uses atmospheric distillation or through a heating process. The purpose of this study is to determine the stages of crude oil processing at the Cepu PPSDM Migas Refinery unit, and the final product of crude oil processing at the Cepu PPSDM Migas Refinery unit. The data collection method used is a literature study conducted by looking for references both journals and books in the library of the Cepu Oil and Gas Human Resources Development Center to determine the refinery system, observations made by direct observation to the unit and control room to obtain temperature data, pressure and capacity of oil entering and leaving crude oil, fuel oil, gas fuel, and interviews were carried out in 2 stages, namely in the control room section and the development of the research process. The results of the research carried out, it was found that the stages of processing crude oil in the refinery unit through the atmospheric distillation process, namely preheating in the Heat Exchanger (HE), heating in the Furnace (F), evaporation in the Evaporator (V), separation in the fractionation column and stripper (C), condensation and cooling in the condenser (CN) and cooler (CL), separation from water in the separator (S) resulted in 10% CA pertasol, 5% CB pertasol, 1% CC pertasol, 59% Solar, residue 25 %.